Management of rectal cancer: the 2016 French guidelines. (February 2017) - Lakkis, Z.; Manceau, G.; Bridoux, V.; Brouquet, A.; Kirzin, S.; Maggiori, L.; de Chaisemartin, C.; Lefevre, J. H.; Panis, Y.; ,
Abstract: Aim: Rectal cancer is a malignant disease requiring multidisciplinary management. In view of the increasing number of studies published over the past decade, a comprehensive update is required to draw recommendations for clinical practice mandated by the French Research Group of Rectal Cancer Surgery and the French National Coloproctology Society. Method: Seven questions summarizing the treatment of rectal cancer were selected. A search for evidence in the literature from January 2004 to December 2015 was performed. A drafting committee and a large group of expert reviewers contributed to validate the statements. Results: Recommendations include the indications for neoadjuvant therapy, the quality criteria for surgical resection, the management of postoperative disordered function, the role of local excision in early rectal cancer, the place of conservative strategies after neoadjuvant treatment, the management of synchronous liver metastases and the indications for adjuvant therapy. A level of evidence was assigned to each statement. Conclusion: The current clinical practice guidelines are useful for the treatment of rectal cancer. Some statements require a higher level of evidence due to a lack of studies.